Article including substrate surface-treated with organosilicon compound, prepreg, printed wiring board, and glass cloth treatment liquid

By using silicone compounds with specific structures for the surface treatment of the substrate, the problems of insufficient heat resistance, alkali resistance and dielectric properties of the glass fiber surface treatment agent are solved, and printed circuit boards with higher adhesion and dielectric properties are achieved.

JP2025018417APending Publication Date: 2025-02-06SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023122103
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In the prior art, the glass fiber surface treatment agent used in printed circuit boards for electronic devices has problems of insufficient heat resistance, alkali resistance and dielectric properties. In particular, the amino group-containing silane coupling agent leads to excessive dielectric loss and the long-chain alkenyl silane has poor stability in aqueous solution.

Method used

The substrate is surface treated with silicone compounds of specific structures, including alkenyl or (meth)acrylate and urea bonds, forming a glass fiber treatment liquid, used to prepare prepregs and printed circuit boards, and improve its adhesion and dielectric properties with resins.

Benefits of technology

The heat resistance, alkali resistance and dielectric properties of the printed circuit board are improved, and its adhesion to the resin is enhanced, forming prepregs and printed circuit boards with more durability and excellent dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018417000001
    Figure 2025018417000001
  • Figure 2025018417000002
    Figure 2025018417000002
  • Figure 2025018417000003
    Figure 2025018417000003
Patent Text Reader

Abstract

To provide an article that yields a prepreg and a printed wiring board with superior durability and dielectric properties.SOLUTION: The present invention provides an article including a substrate surface-treated with an organosilicon compound represented by formula (1), where R1 is a hydrogen atom or an alkyl group, each R2 is a hydrogen atom, an alkyl group, an aryl group or a group represented by the formula (2), at least one of R2 is the group represented by the formula (2), m is an integer of 1-3, n is an integer of 1-12, and k is 0 or 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an article, a prepreg, a printed wiring board, and a glass cloth treatment liquid containing the organosilicon compound, the article comprising a substrate surface-treated with the organosilicon compound. [Background technology]

[0002] As electronic devices such as tablet terminals and smartphones become more powerful and communicate at higher speeds, the printed wiring boards used in these devices are becoming increasingly dense and extremely thin, while at the same time offering lower dielectric constants and lower dielectric loss tangents.As insulating materials for these printed wiring boards, laminates made by laminating prepregs using inorganic fillers and glass cloth as reinforcing materials for thermosetting resins such as epoxy resins and thermosetting polyphenylene ether resins (hereinafter referred to as "matrix resins") and then curing them under heat and pressure are widely used. The reinforcing materials used in these applications are surface-treated with a silane coupling agent, and the organic functional groups of the silane coupling agent react with the organic functional groups of the matrix resin, improving the adhesion between the reinforcing material, such as glass cloth, and the matrix resin. Surface treatment may involve coating the substrate with the silane coupling agent itself, or it may involve treatment with a solution to achieve uniform treatment. When using a solution, it is important to be able to handle the agent as an aqueous solution without using a solvent such as methanol, particularly from the perspective of reducing the environmental impact.

[0003] A representative silane coupling agent used in the glass cloth treatment liquid is 3-methacryloyloxypropyltrimethoxysilane as reported in Patent Document 1. However, laminates using glass cloth whose surface has been treated with 3-methacryloxypropyltrimethoxysilane have poor solder heat resistance and alkali resistance, and have issues with reliability.

[0004] Patent Document 2 proposes a glass cloth that is surface-treated with a silane coupling agent having at least one organic functional group, which is an amino group and an unsaturated double bond, and reports that prepregs and printed wiring boards using this glass cloth have low moisture absorption, excellent heat resistance, and excellent insulation reliability. However, the glass cloth surface-treated with such a silane coupling agent having an amino group tends to have a high dielectric tangent due to the polarity of the amino group, and there is also room for improvement in the alkali resistance of the laminate using the glass cloth.

[0005] On the other hand, Patent Documents 3 and 4 report that the dielectric properties, heat resistance, and moist heat resistance of a resin can be improved by using a filler treated with an alkenyl group-containing silane coupling agent that does not contain polar atoms such as N atoms or O atoms. However, there is still room for improvement. In particular, long-chain alkenylsilanes having carbon numbers of 6 or 8, for example, have low hydrophilicity, which means that they require the use of alcohol in combination when forming an aqueous solution, and the storage stability of the aqueous solution is low. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2020 / 194772 [Patent Document 2] JP 2019-81987 A [Patent Document 3] Patent No. 6684822 [Patent Document 4] International Publication No. 2019 / 103082 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above problems, and has an object to provide an article that can provide a prepreg or printed wiring board having excellent durability and dielectric properties. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and have found that when an article containing a substrate surface-treated with a specific organosilicon compound having an alkenyl group or a (meth)acrylic group and a urea bond is used in a prepreg or printed wiring board, the dielectric properties of the substrate can be improved, and that a solution in which the organosilicon compound is dissolved in a solvent containing water gives a surface-treated glass cloth capable of forming a highly reliable laminate, and is therefore suitable as a glass cloth treatment liquid, thus completing the present invention. Note that in the present invention, the (meth)acrylic group means a methacryl group or an acrylic group.

[0009] That is, the present invention provides 1. An article comprising a substrate surface-treated with an organosilicon compound represented by the following formula (1): [ka] [In the formula, Me is a methyl group, and R 1 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a group represented by the following formula (2): [ka] (In the formula, R 3 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, 3 At least one of the groups is an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, and the wavy line represents the bonding site with the nitrogen atom.) Whereas R 2at least one of the above is a group represented by formula (2), m is an integer of 1 to 3, n is an integer of 1 to 12, and k is 0 or 1. 2. R 1 are each independently a hydrogen atom, a methyl group, or an ethyl group; R 3 are each independently a hydrogen atom, a methyl group, a phenyl group, an allyl group, or a 2-methacryloyloxyethyl group, and R 3 2. The article according to 1, wherein at least one of the groups is an allyl group or a 2-methacryloyloxyethyl group. 3. The article according to 1 or 2, wherein the substrate is an inorganic material. 4. The article according to 3, wherein the inorganic material is silica particles or glass fibers. 5. A prepreg comprising the article according to any one of 1 to 4 and a matrix resin. 6. A printed wiring board comprising the prepreg according to 5. 7. A solution in which an organosilicon compound represented by the following formula (1) is dissolved in a solvent containing water: [ka] [In the formula, Me is a methyl group, and R 1 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a group represented by the following formula (2): [ka] (In the formula, R 3 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, 3 At least one of the groups is an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, and the wavy line represents the bonding site with the nitrogen atom.) Whereas R 2 at least one of the above is a group represented by formula (2), m is an integer of 1 to 3, n is an integer of 1 to 12, and k is 0 or 1. 8. R 1 are each independently a hydrogen atom, a methyl group, or an ethyl group; R 3 are each independently a hydrogen atom, a methyl group, a phenyl group, an allyl group, or a 2-methacryloyloxyethyl group, and R 3 8. The solution according to 7, wherein at least one of the groups is an allyl group or a 2-methacryloyloxyethyl group. 9. A glass cloth treatment solution comprising the solution according to 7 or 8. to provide. Effect of the Invention

[0010] The article of the present invention has excellent adhesion to resins and dielectric properties and can therefore be suitably used as a reinforcing material for prepregs, printed wiring boards, and the like. By using the article, it is possible to obtain prepregs, printed wiring boards, and the like that have excellent durability and dielectric properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. [Goods] The article of the present invention comprises a substrate that has been surface-treated with an organosilicon compound represented by the following formula (1) (hereinafter, sometimes referred to as compound (1)). (1) Organosilicon compounds The organosilicon compound used in the present invention is represented by the following formula (1): The organosilicon compound represented by the following formula (1) is applied to the surface of a substrate, and then heated and dried to obtain a substrate surface-treated with this organosilicon compound.

[0012] [ka]

[0013] In the above formula, Me is a methyl group, and R1 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a group represented by the following formula (2):

[0014] [ka] (In the formula, the wavy line represents the bond to the nitrogen atom.)

[0015] In the above formula (1), R 1 The alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. Among these, R 1 is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, even more preferably a methyl group or an ethyl group, and still more preferably a methyl group.

[0016] R 2 As the alkyl group having 1 to 10 carbon atoms, R 1 Examples of the alkyl group include the same groups as those exemplified in the above, and are preferably alkyl groups having 1 to 6 carbon atoms, and more preferably alkyl groups having 1 to 3 carbon atoms. Specific examples of the aryl group having 6 to 20 carbon atoms include phenyl, α-naphthyl, and β-naphthyl groups, and are preferably aryl groups having 6 to 10 carbon atoms, and more preferably aryl groups having 6 to 8 carbon atoms. However, R 2 At least one, preferably one or two, more preferably one of R is a group represented by the above formula (2). 2 Among these, a hydrogen atom is preferred as the group other than the above formula (2).

[0017] In the above formula (2), R 3 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group. R 3 As the alkyl group having 1 to 10 carbon atoms, R 1 Examples of the alkyl group include the same groups as those exemplified in the above, and are preferably alkyl groups having 1 to 6 carbon atoms, and more preferably alkyl groups having 1 to 3 carbon atoms. Specific examples of the aryl group having 6 to 20 carbon atoms include R 2 Examples of the aryl group include the same groups as those exemplified in 1., and an aryl group having preferably 6 to 10 carbon atoms, more preferably 6 to 8 carbon atoms, is mentioned. Specific examples of the alkenyl group having 2 to 10 carbon atoms include vinyl, allyl, butenyl, hexenyl, and octenyl groups, and are preferably alkenyl groups having 2 to 6 carbon atoms, more preferably vinyl and allyl groups, and even more preferably allyl groups. Examples of the alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group include 2-acryloyloxyethyl, 2-methacryloyloxyethyl, 3-acryloyloxypropyl, and 3-methacryloyloxypropyl groups, of which 2-acryloyloxyethyl and 2-methacryloyloxyethyl groups are preferred, and 2-methacryloyloxyethyl group is more preferred. Among these, R 3 is preferably a hydrogen atom, a methyl group, a phenyl group, an allyl group, or a 2-methacryloyloxyethyl group. However, R 3 At least one, preferably one or two, more preferably one of these is an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, and further preferably an allyl group or a 2-methacryloyloxyethyl group.

[0018] Examples of the group represented by the above formula (2) include, but are not limited to, the following: [ka] (In the formula, the wavy line represents the bond to the nitrogen atom.)

[0019] m represents an integer of 1 to 3, preferably 2 or 3, and more preferably 3. n represents an integer of 1 to 12, and from the viewpoint of raw material procurement, an integer of 1 to 8 is preferable, an integer of 1 to 4 is more preferable, and 3 is even more preferable. k is 0 or 1.

[0020] The compound (1) used in the present invention is preferably one represented by the following formulas (3) to (8). [ka] (In the formula, Me, R 1 , m and n are the same as above. R represents a hydrogen atom or a phenyl group.

[0021] The method for producing compound (1) is not particularly limited, but examples thereof include a method of reacting an alkoxysilane having an isocyanato group (-NCO) with a compound having an amino group and a radical polymerizable group, such as allylamine.

[0022] Specific examples of alkoxysilanes having an isocyanato group include 3-isocyanatopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropylmethyldimethoxysilane, 3-isocyanatopropylmethyldiethoxysilane, 3-isocyanatopropylethyldimethoxysilane, and 3-isocyanatopropylethyldiethoxysilane. Examples of the compound having an amino group and a radically polymerizable group include, in addition to allylamine, diallylamine, allylaniline, and the like. The reaction ratio between the alkoxysilane having an isocyanato group and the compound having an amino group and a radical polymerizable group is not particularly limited, but the amount of the compound having an amino group and a radical polymerizable group per 1 mole of the alkoxysilane having an isocyanato group is preferably 0.8 to 1.5 moles, and more preferably 0.9 to 1.2 moles.

[0023] Further, examples of the method for producing compound (1) include a method in which an alkoxysilane having an amino group is reacted with a compound having an isocyanato group and a radically polymerizable group, such as 2-methacryloyloxyethyl isocyanate.

[0024] Specific examples of alkoxysilanes having an amino group include 3-aminopropyltrimethoxysilane, (N-(2-aminoethyl)-3-aminopropyl)trimethoxysilane, (N-(2-aminoethyl)-3-aminopropyl)triethoxysilane, and (N-(2-aminoethyl)-3-aminopropyl)methyldimethoxysilane. Examples of the compound having an isocyanato group and a radically polymerizable group include 2-acryloyloxyethyl isocyanate in addition to 2-methacryloyloxyethyl isocyanate. The reaction ratio between the alkoxysilane having an amino group and the compound having an isocyanato group and a radical polymerizable group is not particularly limited, but the amount of the compound having an amino group and a radical polymerizable group per 1 mole of the alkoxysilane having an amino group is preferably 0.8 to 1.5 moles, and more preferably 0.9 to 1.2 moles.

[0025] In the above reaction, a solvent may be used as necessary. The solvent is not particularly limited as long as it is non-reactive with the isocyanato group, amino group, and radical polymerizable group contained in the raw material, and specific examples thereof include aliphatic hydrocarbon solvents such as pentane, hexane, heptane, and decane; ether solvents such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; amide solvents such as formamide, dimethylformamide, and N-methylpyrrolidone; and aromatic hydrocarbon solvents such as benzene, toluene, and xylene.

[0026] The reaction temperature in the above reaction is not particularly limited, but is preferably 0 to 200°C, more preferably 0 to 80°C, and even more preferably 10 to 60°C, from the viewpoints of productivity and suppression of side reactions. The reaction time is not particularly limited, but is preferably from 10 minutes to 60 hours, more preferably from 1 to 30 hours, and even more preferably from 1 to 20 hours.

[0027] (2) Base material The substrate in the article of the present invention is not particularly limited, but is preferably an inorganic material, and specific examples thereof include inorganic particles (inorganic fillers) such as silica, titania, zirconia, calcium carbonate, magnesium carbonate, alumina, magnesium oxide, aluminum hydroxide, magnesium hydroxide, talc, clay, and mica; glass fibers such as monofilaments, glass strands, glass yarns, glass rovings, twisted yarns, bulky processed yarns, chopped strands, milled fibers, staple fibers, glass cloths, nonwoven fabrics, tapes, and nets; ceramics such as porcelain, cement, enamel, and fine ceramics; metals such as iron, aluminum, copper, silver, gold, and magnesium. Among these, silica particles or glass fibers are particularly preferred from the viewpoint of the reactivity of the alkoxysilyl group.

[0028] (2-1) Silica particles The silica particles are not particularly limited, and examples thereof include colloidal silica, fumed silica, crystalline silica, and fused silica. In the case of colloidal silica, the silica particles are preferably colloidally dispersed in a medium such as water or an organic solvent, and commercially available water-dispersed or organic-dispersed types can be used. The shape of the silica particles is not particularly limited, and examples thereof include spherical and irregular shapes, but spherical shapes are preferred, and the average particle size is also not particularly limited, but a median size measured by dynamic light scattering is preferably 1 to 100 nm. As such silica particles, commercially available products can be used, and examples thereof include Snowtex O, OS, O40, OL, methanol silica sol, IPA-ST, IBA-ST, PMA-ST, MEK-ST, and the like manufactured by Nissan Chemical Industries, Ltd. Among these, Snowtex O is preferred.

[0029] (2-2) Glass fiber As the glass fiber, glass cloth is preferred. The glass yarn constituting the glass cloth that is the substrate before surface treatment is not particularly limited, and glass compositions of known glass compositions can be used. Specific examples thereof include E glass, L glass, L2 glass, NE glass, NE2 glass, S glass, T glass, UT glass, LU glass, D glass, silica glass, etc., and one or more types of glass cloth selected from the group consisting of these glasses are used depending on the application. Among these, glass cloth selected from L glass, L2 glass, NE glass, NE2 glass, LU glass, and silica glass is preferred in terms of dielectric properties. In the present invention, the dielectric loss tangent at 10 GHz refers to a value measured by the method described in JIS R 1641:2007 (Method for measuring microwave dielectric properties of fine ceramic substrates).

[0030] It is preferable to remove organic substances such as a sizing agent attached to the surface of the glass cloth before surface treatment with the organosilicon compound, since the surface of the glass cloth can be treated evenly with the organosilicon compound. Methods for removing the organic substances include heat cleaning treatment, corona treatment, and hot water washing treatment.

[0031] The thickness of the glass cloth is preferably 6 to 200 μm, more preferably 10 to 100 μm, and the mass per unit area is preferably 5 to 200 g / m 2 and 10 to 100 g / m 2 The glass cloth is more preferable.

[0032] (3) Manufacturing method of the article The article of the present invention includes a substrate that has been surface-treated as described above. It is preferable that the surface-treated substrate itself is used as the article. In this case, the method for producing the article of the present invention is not particularly limited, and the article of the present invention can be produced by appropriately selecting a surface treatment method for the substrate depending on the type, shape, etc. of the substrate.

[0033] (3-1) Method for producing surface-treated silica particles When silica particles are used as the substrate, for example, a method of surface treatment in a solvent may be used. When a resin is used in a post-process, a kneading treatment in which compound (1) is added to and mixed with a compound consisting of untreated silica particles and a resin dispersion medium may be used. However, the method of surface treatment in a solvent is preferred. The solvent may be one that is generally easily available, and examples thereof include water; alcohol-based solvents such as methanol, ethanol, and isopropyl alcohol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; hydrocarbon-based solvents such as hexane, toluene, and xylene; ether-based solvents such as diethyl ether, tetrahydrofuran, and dioxane; and ester-based solvents such as ethyl acetate and butyl acetate. One type of solvent may be used alone, or two or more types may be mixed and used.

[0034] In the present invention, it is preferable to use a colloidal silica dispersion in which silica particles are dispersed in the above-mentioned solvent, and the surface treatment can be performed by adding compound (1) to this dispersion and mixing and stirring. The treatment conditions are not particularly limited, but can be, for example, preferably 20 to 150°C, more preferably 25 to 120°C, and preferably 1 to 10 hours, more preferably 1 to 6 hours.

[0035] The amount of compound (1) added is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, in total, based on 100 parts by mass of the silica particles. Compound (1) can be used alone or in combination of two or more kinds.

[0036] In the surface treatment of the silica particles, an organosilicon compound other than the compound (1), such as an alkoxy group-containing organosilicon compound or a silazane structure-containing compound, may be used in combination. Specific examples of the alkoxy group-containing organosilicon compound include 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, p-styryltrimethoxysilane, and 8-methacryloxyoctyltrimethoxysilane. Specific examples of the silazane structure-containing compound include low-molecular-weight silazane compounds such as 1,1,3,3-tetramethyldisilazane, hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, octamethyltrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane, and 1,1,3,3,5,5-trimethyltrivinylcyclotrisilazane. These may be used alone or in combination of two or more.

[0037] When an organosilicon compound other than compound (1) is used, it may be added simultaneously with compound (1), or it may be added before or after the surface treatment with compound (1); however, it is preferable to add it after the surface treatment with compound (1). When an organosilicon compound other than the compound (1) is used, the total amount added is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the silica particles.

[0038] After the surface treatment, the solvent is removed by a separation means such as filtration or liquid separation, and the particles are washed and dried to obtain surface-treated silica particles. The drying conditions are not particularly limited, but are preferably 60 to 180°C, more preferably 80 to 150°C, and are preferably 5 minutes to 2 hours, more preferably 10 minutes to 1 hour, for example. The above production method can be similarly applied to inorganic particles and inorganic fillers other than silica particles.

[0039] (3-2) Manufacturing method of surface-treated glass fiber When glass fibers are used as the substrate, glass cloth is particularly preferred. When the surface of glass cloth is treated, it can be treated with a solution in which the organosilicon compound of the present invention is dissolved in a solvent containing water. The surface treatment method of the glass cloth is not particularly limited, but specifically, flow coating (immersion method), spin coating, etc. can be mentioned as a method for directly treating the substrate, and other known methods such as spray coating, dip coating, roller coating, brush coating, bar coating, etc. can be appropriately selected and used. After that, it is preferable to perform a heating and drying treatment. As a representative treatment condition, for example, it is preferable to heat and dry at 60 to 180°C, preferably 80 to 150°C for 5 minutes to 2 hours, and to remove the solvent and simultaneously chemically react the organosilicon compound in the solution with the substrate surface. The above manufacturing method can be similarly applied to substrates other than glass cloth.

[0040] [Solution / Glass cloth treatment solution] The solution of the present invention is a solution in which the organosilicon compound of the present invention is dissolved in a solvent containing water, and the solution of the present invention is preferably used as a glass cloth treatment liquid (hereinafter, sometimes referred to as a "treatment liquid") used for surface treatment of glass cloth as described above. From the viewpoints of storage stability and productivity, the content of the organosilicon compound in the treatment liquid of the present invention is preferably 0.001 to 10.0 mass %, more preferably 0.05 to 5.0 mass %, and more preferably 0.05 to 2.0 mass %, in terms of solid content relative to the entire treatment liquid.

[0041] The method for producing the glass cloth treatment liquid of the present invention is not particularly limited, and the glass cloth treatment liquid can be produced by adding and dissolving the organosilicon compound of the present invention in a solvent containing water. The temperature when the organosilicon compound is added to the solvent is preferably 10 to 50°C, more preferably 15 to 40°C.

[0042] The glass cloth treatment liquid of the present invention may contain, in addition to the organosilicon compound of the present invention and water, an organic solvent within a range that does not impair the effects of the present invention. The organic solvent is not particularly limited, but is preferably an organic solvent having excellent compatibility with water. Examples of the organic solvent include alcohols such as methanol, ethanol, and isopropanol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; esters such as ethyl acetate; and ketones such as acetone and methyl ethyl ketone. One type may be used alone, or two or more types may be used in combination. When an organic solvent is used, its blending amount is not particularly limited, but is preferably 10 to 70% by mass, and more preferably 20 to 60% by mass, of the entire treatment liquid.

[0043] The water contained in the glass cloth treatment liquid of the present invention is preferably adjusted to be acidic from the viewpoint of storage stability. Examples of the acid to be used for adjusting the acidity include organic acids such as formic acid, acetic acid, and citric acid, and inorganic acids such as hydrochloric acid. When an acid is used, the amount of the acid added is preferably 0.001 to 0.5% by mass, more preferably 0.01 to 0.1% by mass, of the total treatment liquid. When an acid is used, the water may be adjusted to be acidic by mixing the acid with water in advance, or the acid may be added to the glass cloth treatment liquid containing the organosilicon compound of the present invention to adjust the acidity.

[0044] The glass cloth treatment liquid of the present invention is preferably an aqueous solution in which the organosilicon compound of the present invention is dissolved in water, and more preferably an aqueous solution in which the organosilicon compound of the present invention is dissolved in water that has been adjusted to be acidic.

[0045] To the glass cloth treatment liquid of the present invention, an alkoxy group-containing organosilicon compound, a silazane compound, etc. other than the organosilicon compound of the present invention can be added, if necessary, to improve the adhesion and bonding with the glass cloth, within a range that does not impair the effects of the present invention. Specific examples of the alkoxy group-containing organosilicon compound and the silazane compound include the same as those exemplified in the method for producing surface-treated silica particles. In addition, other additives may be added to the glass cloth treatment liquid of the present invention as necessary within the scope of not impairing the effects of the present invention. Specific examples of other additives include water-soluble resins, curing catalysts, physical property adjusters for adjusting the tensile properties of the resulting cured coating, storage stability improvers, surfactants, metal deactivators, antiozonants, lubricants, pigments, etc.

[0046] [Prepreg] The prepreg of the present invention comprises the above-mentioned article and a matrix resin. The article containing the substrate surface-treated with the organosilicon compound of the present invention can be mixed with a matrix resin to form a prepreg. In particular, when the substrate (article) is surface-treated silica particles or surface-treated glass cloth, the resulting prepreg has excellent strength and can be suitably used, for example, for printed wiring boards.

[0047] (1) Goods The article contained in the prepreg is not particularly limited as long as it contains a substrate that has been surface-treated with the organosilicon compound of the present invention, but it is preferable that the substrate itself is a surface-treated substrate, such as surface-treated silica particles or surface-treated glass cloth.

[0048] (2) Matrix resin The matrix resin used in the prepreg of the present invention is not particularly limited and can be appropriately selected from conventionally known resins. Examples of the matrix resin include thermosetting silicone resins, polyimide resins, maleimide resins, epoxy resins, cyanate resins, (meth)acrylic resins, polyphenylene ether resins, and polytetrafluoroethylene resins. Of these, polyphenylene ether resins and maleimide resins are preferred.

[0049] Other components can be added to the matrix resin in the present invention in order to accelerate curing of the resin, increase its strength, etc. Specific examples of other components include inorganic fillers, flame retardants, additives, reaction initiators, crosslinking agents, curing agents, organic resins other than the matrix resin, etc. When other components are blended, the amount of the other components added is preferably 1 to 900 parts by mass, more preferably 10 to 500 parts by mass, and even more preferably 10 to 100 parts by mass, relative to 100 parts by mass of the matrix resin.

[0050] (3) Manufacturing method of prepreg The method for producing the prepreg of the present invention is not particularly limited, and general methods for producing glass cloth-containing substrates, films, prepregs, etc. can be applied. For example, a method in which a molten matrix resin or a solution containing a matrix resin is mixed with a surface-treated inorganic filler, and the obtained resin is applied to a glass cloth to impregnate it, or a method in which a matrix resin is applied to a surface-treated glass cloth to impregnate it, etc. can be used.

[0051] (3-1) Method for producing prepreg containing surface-treated silica particles When surface-treated silica particles are used as the article, a prepreg containing the surface-treated silica particles can be obtained by mixing a matrix resin, the surface-treated silica particles, and other components as necessary, and applying the resulting resin or solution to a glass cloth and impregnating it therewith.

[0052] To improve and ensure the coating property, the matrix resin may be diluted with a solvent. Depending on the solubility property of the matrix resin, one organic solvent may be used alone or two or more organic solvents may be used in combination. Examples of organic solvents include alcohols such as methanol, ethanol, isopropanol, and n-butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; glycol ethers such as ethylene glycol and propylene glycol; aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; and alkyl ethers such as diethyl ether, diisopropyl ether, and dibutyl ether.

[0053] The method for mixing the matrix resin and the surface-treated silica particles is not particularly limited, but examples include a method in which the matrix resin or a solution containing the matrix resin, the surface-treated silica particles, and other components, if necessary, are mixed by a conventionally known method and stirred for about 10 minutes to 1 hour.

[0054] The amount of the surface-treated silica particles added is preferably 10 to 300 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 60 to 150 parts by mass, per 100 parts by mass of the matrix resin (the amount of matrix resin contained in the case of a solution). The glass cloth may be surface-untreated or surface-treated, and one type may be used alone or two or more types may be used in combination.

[0055] Next, the matrix resin containing the surface-treated silica particles is applied to the glass cloth and impregnated therein. The prepreg of the present invention can be produced, for example, in accordance with a general method for applying a curable resin composition to glass cloth fibers (coating method). Representative coating methods include direct gravure coater, chamber doctor coater, offset gravure coater, single roll kiss coater, reverse kiss coater, bar coater, reverse roll coater, slotter die coater, air doctor coater, positive rotation roll coater, blade coater, knife coater, impregnation coater, MB coater, MB reverse coater, etc.

[0056] The amount of the matrix resin attached to the glass cloth is preferably 10 to 80% by mass, more preferably 20 to 70% by mass. Within this range, the amount of the matrix resin attached to the glass cloth is appropriate, and there is an effect of improving the adhesion and bonding with the matrix resin, and the strength of the wiring board. If the amount of the matrix resin attached is 10% by mass or more, when the prepreg and the copper foil are laminated to produce a board, the amount of the matrix resin attached to the copper foil is not too small, and sufficient peel strength with the copper foil can be obtained. In addition, if the amount of the matrix resin attached is 80% by mass or less, the amount of the matrix resin is not too large, and resin flow during pressing is unlikely to occur, which is preferable. The amount of the matrix resin attached here indicates the mass % of the matrix resin relative to the mass of the entire prepreg.

[0057] Conditions vary depending on the matrix resin used, but for example, after application, the resin can be dried and then heated at 50 to 300° C. for 1 minute to 24 hours for curing.

[0058] (3-2) Method for manufacturing prepreg containing surface-treated glass cloth When a surface-treated glass cloth is used as the article, a prepreg containing the surface-treated glass cloth can be obtained by mixing a matrix resin or a solution containing the matrix resin and, if necessary, other components, and impregnating the surface-treated glass cloth with the obtained resin or solution. The specific manufacturing method is the same as that in the case of using surface-treated silica particles. Surface-treated silica particles may be added to the matrix resin, and in that case, the amount added is the same as above.

[0059] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 400 μm, more preferably 30 to 300 μm, and even more preferably 40 to 200 μm. Within this range, for example, when the prepreg of the present invention is used for a printed wiring board, a board such as a copper-clad laminate can be well prepared. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the matrix resin may be dissolved in a solvent, impregnated into glass cloth, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-stage.

[0060] [Printed wiring board] The printed wiring board of the present invention is obtained using a prepreg including the article of the present invention. The method for producing the printed wiring board of the present invention is not particularly limited, and a general method for producing a printed wiring board can be applied. A specific example is a method in which the prepreg of the present invention and a copper foil are stacked and pressed, and then heat-cured to produce a substrate as a copper-clad laminate. The method for producing the copper-clad laminate is not particularly limited, and can be produced, for example, by using 1 to 20 sheets, preferably 2 to 10 sheets, of the above prepreg, arranging copper foil on one or both sides of the prepreg, pressing, and then heat-curing.

[0061] The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate with high reliability can be formed. The molding conditions for the copper-clad laminate are not particularly limited, but for example, it can be molded using a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, or the like, at a temperature of 100 to 400° C., a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. In addition, the prepreg of the present invention, the copper foil, and the wiring board for the inner layer can be combined and molded to form a copper-clad laminate.

[0062] The method of circuit processing is not particularly limited, and examples thereof include circuit formation processing methods such as drilling, metal plating, etching of metal foil, etc. In addition, a printed wiring board may be produced by a build-up method in which a composition containing a matrix resin or the prepreg of the present invention and copper foil are sequentially laminated. EXAMPLES

[0063] The present invention will be described in more detail below with reference to synthesis examples, examples, and comparative examples, but the present invention is not limited to these examples. In the following formulas, Me represents a methyl group, and Et represents an ethyl group. Infrared absorption (IR) spectrum measurements were performed using a Fourier transform infrared spectrophotometer Nicolet 6700 manufactured by Thermo Fisher Scientific.

[0064] [1] Synthesis of organosilicon compounds [Synthesis Example 1] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 80.0g (1.40mol) of N-allylamine (Tokyo Chemical Industry Co., Ltd.) was placed, and 287.7g (1.40mol) of 3-isocyanatopropyltrimethoxysilane (KBM-9007, Shin-Etsu Chemical Co., Ltd.) was added dropwise using a dropping funnel at 25°C, and then the mixture was stirred at 40°C for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C, and the compound (3a) represented by the following formula was obtained.

[0065] [ka]

[0066] [Synthesis Example 2] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 140.0g (1.05mol) of N-allylaniline (Tokyo Chemical Industry Co., Ltd.) was placed, and 215.8g (1.05mol) of 3-isocyanatopropyltrimethoxysilane (KBM-9007, Shin-Etsu Chemical Co., Ltd.) was added dropwise using a dropping funnel at a temperature of 80°C, and then the mixture was stirred at 80°C for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C, and the compound (3b) represented by the following formula was obtained.

[0067] [ka]

[0068] [Synthesis Example 3] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 80.0g (1.40mol) of N-allylamine (Tokyo Chemical Industry Co., Ltd.) was placed, and 346.6g (1.40mol) of 3-isocyanatopropyltrimethoxysilane (KBM-9007, Shin-Etsu Chemical Co., Ltd.) was added dropwise at 25℃ using a dropping funnel, and then the mixture was stirred at 40℃ for 8 hours. The reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25℃ to obtain the compound (3c) represented by the following formula.

[0069] [ka]

[0070] [Synthesis Example 4] In a 500 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 100.0 g (1.03 mol) of diallylamine (Tokyo Chemical Industry Co., Ltd.) was placed, and 211.3 g (1.03 mol) of 3-isocyanatopropyltrimethoxysilane (KBM-9007, Shin-Etsu Chemical Co., Ltd.) was added dropwise at 25°C using a dropping funnel, and then the mixture was stirred at 40°C for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C, and the compound (4a) represented by the following formula was obtained.

[0071] [ka]

[0072] [Synthesis Example 5] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 60.0g (0.62mol) of diallylamine (Tokyo Chemical Industry Co., Ltd.) was placed, and 152.7g (0.62mol) of 3-isocyanatopropyltrimethoxysilane (KBM-9007, Shin-Etsu Chemical Co., Ltd.) was added dropwise at 25℃ using a dropping funnel, and then the mixture was stirred at 40℃ for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25℃ to obtain the compound (4b) represented by the following formula.

[0073] [ka] [Synthesis Example 6] In a 500 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 60.0 g (0.62 mol) of diallylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was placed, and 117.4 g (0.62 mol) of 3-isocyanatopropylmethyldimethoxysilane was added dropwise using the dropping funnel at 25°C, followed by stirring for 8 hours at 40°C. The reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C, and the compound (4c) represented by the following formula was obtained.

[0074] [ka]

[0075] [Synthesis Example 7] 200.0g (1.12 mol) of 3-aminopropyltrimethoxysilane (KBM-903, Shin-Etsu Chemical Co., Ltd.) was placed in a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, and 173.1g (1.12 mol) of 2-methacryloyloxyethyl isocyanate (Kalends MOI, Resonac Co., Ltd.) was added dropwise at 25°C using a dropping funnel, and then the mixture was stirred at 40°C for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C to obtain the compound (5a) represented by the following formula.

[0076] [ka]

[0077] [Synthesis Example 8] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 150g (0.67mol) of (N-(2-aminoethyl)-3-aminopropyl)trimethoxysilane (KBM-603, Shin-Etsu Chemical Co., Ltd.) was placed, and 104.6g (0.67mol) of 2-methacryloyloxyethyl isocyanate (Kalends MOI, Resonac Co., Ltd.) was added dropwise at 25°C using a dropping funnel, and then the mixture was stirred at 40°C for 8 hours. The reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C to obtain the compound (6a) represented by the following formula.

[0078] [ka]

[0079] [Synthesis Example 9] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 177g (0.67mol) of (N-(2-aminoethyl)-3-aminopropyl)triethoxysilane (KBE-603, Shin-Etsu Chemical Co., Ltd.) was placed, and 104.6g (0.67mol) of 2-methacryloyloxyethyl isocyanate (Kalends MOI, Resonaq Co., Ltd.) was added dropwise at 25°C using a dropping funnel, and then the mixture was stirred at 40°C for 8 hours. The reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C to obtain the compound (6b) represented by the following formula.

[0080] [ka]

[0081] [Synthesis Example 10] In a 500mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 138g (0.67mol) of (N-(2-aminoethyl)-3-aminopropyl)methyldimethoxysilane (KBM-602, Shin-Etsu Chemical Co., Ltd.) was placed, and 104.6g (0.67mol) of 2-methacryloyloxyethyl isocyanate (Kalends MOI, Resonac Co., Ltd.) was added dropwise at 25°C using a dropping funnel, and then the mixture was stirred at 40°C for 8 hours. The reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C to obtain the compound (6c) represented by the following formula.

[0082] [ka]

[0083] [Synthesis Example 11] In a 500 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 150 g (0.67 mol) of (N-(2-aminoethyl)-3-aminopropyl)trimethoxysilane (KBM-603, Shin-Etsu Chemical Co., Ltd.) was placed, and 136.0 g (0.88 mol) of 2-methacryloyloxyethyl isocyanate (Kalends MOI, Resonac Co., Ltd.) was added dropwise at 25°C using a dropping funnel. The mixture was then stirred at 40°C for 8 hours, and the reaction was terminated when it was confirmed that the absorption peak derived from the isocyanato group in the IR spectrum had disappeared. The mixture was cooled to 25°C to obtain a mixture M of compounds (6a), (7a) and (8a) represented by the following formula.

[0084] [ka]

[0085] [2] Preparation of aqueous solution [Examples 1-1 to 1-11, Comparative Examples 1-1 to 1-3] 99.5 parts by mass of ion-exchanged water and 0.05 parts by mass of acetic acid were mixed and stirred at 25°C, while 0.5 parts by mass of each of the organosilicon compounds obtained in Synthesis Examples 1 to 10 above, the mixture M obtained in Synthesis Example 11 above, or the organosilicon compounds A to C below were each added dropwise to produce an aqueous solution. The aqueous solutions thus obtained were subjected to the following evaluations, and the results are shown in Table 1.

[0086] Organosilicon compound A: 3-methacryloyloxypropyltrimethoxysilane (product name: KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound B: 8-methacryloyloxyoctyltrimethoxysilane (product name: KBM-5083, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound C: 7-octenyltrimethoxysilane (product name: KBM-1083, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0087] [Stability of aqueous solution] The resulting aqueous solution was allowed to stand in an environment of 25° C. for 1 hour and for 3 days, and then the appearance was visually inspected and evaluated according to the following criteria. ◯: Completely dissolved, forming a homogeneous aqueous solution. ×: Insoluble matter precipitated.

[0088] [Table 1]

[0089] As shown in Table 1, the aqueous solutions of Examples 1-1 to 1-11 had excellent storage stability. On the other hand, the aqueous solution of Comparative Example 1-1 in which 3-methacryloyloxypropyltrimethoxysilane was dissolved had low storage stability, and when a silane coupling agent with a long alkylene chain was used as in Comparative Examples 1-2 and 1-3, it was difficult to prepare the aqueous solution.

[0090] [3] Manufacturing of surface-treated silica particles [Examples 2-1 to 2-11, Comparative Example 2-1] 625 g of silica sol obtained by concentrating a silica concentration of a commercially available acidic aqueous silica sol (trade name: Snowtex O, manufactured by Nissan Chemical Industries, Ltd.) to 40% by mass, and 1125 g of isopropyl alcohol were stirred in a 2-liter glass separable flask equipped with a stirrer, a dropping funnel, a cooling tube, and a thermometer while bubbling air at 25°C. 30 g of each of the organosilicon compounds obtained in the above Synthesis Examples 1 to 10, the mixture M obtained in the above Synthesis Example 11, or the above organosilicon compound A was dropped into the flask, and the temperature was raised to 78°C and stirring was continued for 4 hours to perform a hydrophobic treatment of the silica sol. Thereafter, the internal temperature was lowered to 70°C, 34 g of hexamethyldisilazane (trade name: HMDS, manufactured by Shin-Etsu Chemical Co., Ltd.) was dropped, and stirring was continued for 2 hours. The solid was filtered, washed with methanol, and then dried under reduced pressure at 110°C for 1 hour to obtain surface-treated silica particles (i) to (xii) shown in Table 2.

[0091] [Table 2]

[0092] [4] Manufacturing of prepregs and substrates using surface-treated silica particles [Examples 3-1 to 3-12, Comparative Examples 3-1 to 3-3] A polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups (Noryl (registered trademark) SA9000 manufactured by SHPP Japan LLC, hereafter referred to as PPE) was mixed with toluene in a mass ratio of 1:1, and the mixed solution was heated and stirred at 80°C for 1 hour to completely dissolve the PPE in the toluene, and then cooled to 25°C to obtain a 50% by mass toluene solution of PPE. Next, according to the compounding ratios (parts by mass) shown in Tables 3 and 4, a 50% by mass toluene solution of the PPE (converted to non-volatile content), a crosslinking agent, an organic resin, surface-treated silica particles, and a curing agent were mixed and stirred for 30 minutes to completely dissolve, thereby obtaining a varnish-like curable composition (resin varnish).

[0093] Next, the obtained resin varnish was impregnated into a glass cloth (manufactured by Nitto Boseki Co., Ltd., #1078 type, WEA1078), and then heated and dried at 120° C. for 3 minutes to obtain a prepreg. At this time, the thickness after curing was adjusted to be about 60 μm. Both sides of one of the obtained prepregs were sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm) and laminated, and then sintered under vacuum conditions at 190°C for 90 minutes at a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, a cured article, evaluation substrate 1, was obtained. In addition, 12 sheets of the prepreg obtained above were stacked, sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm), and laminated under vacuum conditions at 220°C for 90 minutes and a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, an evaluation substrate 2 was obtained.

[0094] The evaluation substrates 1 and 2 prepared by the above procedure were evaluated by the methods described below. The results are shown in Tables 3 and 4 below. [Dielectric properties] For each of the evaluation boards 2 produced above from which the copper foil had been removed, the relative dielectric constant and the dielectric loss tangent at 10 GHz were measured by a cavity resonator perturbation method using a network analyzer (E5063-2D5 manufactured by Keysight Corporation). [Copper foil adhesion strength] The peel strength (copper foil adhesion strength) of each of the evaluation boards 1 prepared above was measured by a method conforming to JIS C 6481. At this time, a pattern with a width of 10 mm and a length of 100 mm was formed on a test piece with a width of 20 mm and a length of 100 mm, and the copper foil was peeled off at a speed of 50 mm / min using a tensile tester, and the peel strength (kN / m) at this time was evaluated as the copper foil adhesion strength.

[0095] [Table 3]

[0096] [Table 4]

[0097] Each component shown in Tables 3 and 4 will be explained below. PPE: PPO Noryl (registered trademark) SA9000 (polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups) manufactured by SABIC Innovative Plastics Co., Ltd. (SHPP Japan LLC) Crosslinking agent 1: TAIC (trademark) (triallyl isocyanurate) manufactured by Nippon Kasei Co., Ltd. Crosslinking agent 2: DCP (tricyclodecane dimethanol dimethacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd. Organic resin: Cray Valley Ricon 100 (styrene butadiene random copolymer) Hardener: NOF Corp. Perbutyl P (1,3-bis(butylperoxyisopropyl)benzene, peroxide)

[0098] As shown in Tables 3 and 4, the printed wiring boards of Examples 3-1 to 3-12, which include prepregs using the surface-treated silica particles of Examples 2-1 to 2-11, are excellent in dielectric properties and copper foil adhesion strength.

[0099] [5] Manufacture of surface-treated glass cloth [Examples 4-1 to 4-11, Comparative Examples 4-1 to 4-3] A glass cloth treatment solution was prepared according to the following procedure, and the glass cloth was subjected to surface treatment. The organosilicon compounds (3a), (3b), (3c), (4a), (4b), (4c), and (5a) obtained in Synthesis Examples 1 to 7 above, or the organosilicon compound A above, were added to an aqueous solution of acetic acid having a concentration of 0.1% by mass so as to give a solids concentration of 0.2% by mass, and the mixture was stirred to prepare a glass cloth treatment liquid. Furthermore, the organosilicon compounds (6a), (6b), and (6c) obtained in Synthesis Examples 8 to 10 above, and the mixture M obtained in Synthesis Example 11 above were each added to a 1.0% by mass aqueous acetic acid solution so that the solid content concentration was 0.2% by mass, and the mixture was stirred to prepare a glass cloth treatment solution. Furthermore, organosilicon compound D shown below was added to ion-exchanged water to a concentration of 0.2% by mass, and the mixture was stirred to prepare a glass cloth treatment liquid. The obtained glass cloth treatment liquid was added to a silica glass cloth (thickness: 95 μm, mass per unit area: 93 g / m 2 ) and then heated and dried at 110°C for 10 minutes to produce a surface-treated glass cloth.

[0100] Organosilicon compound D: 3-aminopropyltrimethoxysilane (product name: KBM-903, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0101] The obtained surface-treated glass cloth was evaluated by the following methods, and the results are shown in Tables 5 and 6 below.

[0102] [Dielectric properties] A rectangular molded piece of 5 cm x 5 cm with a thickness of 0.30 mm was prepared. A network analyzer (Keysight: E5063-2D5) was connected to a strip line (Keycom Co., Ltd.) to measure the dielectric constant and dielectric loss tangent of the molded piece at a frequency of 10 GHz. The measurement results of a glass cloth that was not surface-treated (Comparative Example 4-1) were converted to 100, and evaluation was performed.

[0103] [5] Manufacturing of prepregs and substrates using surface-treated glass cloth [Examples 5-1 to 5-11, Comparative Examples 5-1 to 5-3] The surface-treated glass cloth obtained in Examples 4-1 to 4-11 and Comparative Examples 4-2 and 4-3 was impregnated with a matrix resin (M-1), and the prepreg was obtained by removing the solvent by heating and drying at 100°C for 10 minutes. Next, one prepreg was heated and cured at 180°C for 60 minutes under a pressure of 5 MPa using a vacuum press to produce an evaluation substrate 3. In Comparative Example 5-1, evaluation substrate 3 was produced in the same manner as in the other Examples and Comparative Examples, except that an untreated silica glass cloth was used. Here, the matrix resin (M-1) is a mixture prepared by adding 122 parts by mass of toluene to 100 parts by mass of a bismaleimide compound (product name: BMI-5000P, manufactured by Designers Inc.) to adjust the resin concentration to 45% by mass, and then adding 2 parts of dicumyl peroxide as a curing catalyst.

[0104] [Solder heat resistance test] Each evaluation board 3 thus obtained was cut into a 5 cm square, boiled in ion-exchanged water for 2 hours, and then immersed in a solder bath at 260°C for 30 seconds. The appearance of the board was visually observed, and boards that did not blister were rated as "good" and boards that blistered were rated as "poor". The results are shown in Tables 5 and 6.

[0105] [Alkaline immersion test] Each evaluation substrate 3 thus obtained was cut into a 5 cm square, which was then immersed in a 1N aqueous solution of sodium hydroxide for 24 hours. The appearance of the cured product was visually observed and evaluated according to the following criteria. The results are shown in Tables 5 and 6. ◯: No whitening or slight whitening at the edge. △: Bleaching extended to near the center. ×: The entire surface was whitened.

[0106] [Table 5]

[0107] [Table 6]

[0108] As shown in Tables 5 and 6, the surface-treated glass cloths of Examples 4-1 to 4-11 had low dielectric tangents, and the printed wiring boards of Examples 5-1 to 5-11 equipped with prepregs using these surface-treated glass cloths exhibited excellent solder heat resistance and alkali resistance. On the other hand, the surface-treated glass cloths of Comparative Examples 4-2 and 4-3 had a high dielectric tangent, and the substrates of Comparative Examples 5-2 and 5-3 using these glass cloths also had low alkali resistance.

Claims

1. An article comprising a substrate that has been surface-treated with an organosilicon compound represented by the following formula (1): 【Chemistry 1】 [In the formula, Me is a methyl group, R 1 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a group represented by the following formula (2): 【Chemistry 2】 (In the formula, R 3 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, 3 At least one of the groups is an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, and the wavy line portion represents the bonding site with the nitrogen atom.) Wherein R is a group represented by 2 At least one of the groups is a group represented by the above formula (2), m is an integer of 1 to 3, n is an integer of 1 to 12, and k is 0 or 1.

2. R 1 are each independently a hydrogen atom, a methyl group, or an ethyl group; R 3 are each independently a hydrogen atom, a methyl group, a phenyl group, an allyl group, or a 2-methacryloyloxyethyl group, and R 3 2. The article according to claim 1, wherein at least one of: is an allyl group or a 2-methacryloyloxyethyl group.

3. 2. The article of claim 1, wherein the substrate is an inorganic material.

4. 4. The article of claim 3, wherein the inorganic material is silica particles or glass fibers.

5. A prepreg comprising the article of claim 1 and a matrix resin.

6. A printed wiring board comprising the prepreg according to claim 5.

7. A solution in which an organosilicon compound represented by the following formula (1) is dissolved in a solvent containing water. 【Chemistry 3】 [In the formula, Me is a methyl group, R 1 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a group represented by the following formula (2): 【Chemistry 4】 (In the formula, R 3 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, 3 At least one of the groups is an alkenyl group having 2 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms substituted with an acryloyloxy group or a methacryloyloxy group, and the wavy line portion represents the bonding site with the nitrogen atom.) Wherein R is a group represented by 2 At least one of the groups is a group represented by the above formula (2), m is an integer of 1 to 3, n is an integer of 1 to 12, and k is 0 or 1.

8. R 1 are each independently a hydrogen atom, a methyl group, or an ethyl group; R 3 are each independently a hydrogen atom, a methyl group, a phenyl group, an allyl group, or a 2-methacryloyloxyethyl group, and R 3 8. The solution according to claim 7, wherein at least one of the groups is an allyl group or a 2-methacryloyloxyethyl group.

9. A glass cloth treatment solution comprising the solution according to claim 7 or 8.

Citation Information

Patent Citations

  • Dental inorganic filler having a silanized surface

    JP2021506906A

  • Vehicular scuff plate and manufacturing method for the same

    JP2022097168A

  • High flexible and high thermal resistant nano-composite composition for forming insulation coating of circuit or metal layer deposited by sputtering in flexible printed circuit boards and manufacturing methode there of

    KR101796995B1

  • Glass cloth, prepreg, and print circuit board

    JP2019081987A

  • High frequency thermosetting resin composition, prepreg, laminated sheet, and printed circuit board using the same

    JP6684822B2